THE EFFECTIVENESS OF BAAMBOOZLE MEDIA ON STUDENTS’ READING COMPREHENSION AT GRADE IX OF SMP NEGERI 5 PEMATANGSIANTAR - Lusia Pebriyani Silaban; Leonita M.E. Manihuruk; Basar Lolo Siahaan; Irene Adryani Nababan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aimed to find out the effect of applying the Discovery Learning method on students’ reading comprehension achievement at SMA Negeri 1 Loura in the academic year 2022/2023. The study applied a quantitative approach with a quasi-experimental design. The population was all the students of class XI IPA, and the sample consisted of two classes: class XI IPA 1 as the experimental group and class XI IPA 2 as the control group. The instrument used was a reading comprehension test in the form of multiple-choice questions. Data were collected through a pre-test, treatment, and post-test. The validity and reliability of the instrument were tested before its use. Data analysis was carried out using statistical calculations, including the t-test formula, to compare the mean scores of the experimental and control groups. The results of the research showed that the mean score of the experimental group after treatment was significantly higher than that of the control group. The statistical analysis confirmed that the application of the Discovery Learning method had a positive effect on improving students’ reading comprehension achievement. In conclusion, the Discovery Learning method can be considered an effective teaching strategy in enhancing students’ reading comprehension, and it is recommended for English teachers to implement this method in the classroom.